PENGEMBANGAN BAHAN AJAR BERBASIS PENDEKATAN DEEP LEARNING DALAM KEMAMPUAN MENGANALISIS TEKS BIOGRAFI KELAS X - Eka Nur Aminatus Sholihah; Laila Tri Lestari; Iib Marzuqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian language instruction regarding biographical texts for Grade X students at MA Matholi’ul Anwar Simo faces challenges because the existing teaching materials fail to optimally develop students' abilities to analyze the structure, linguistic elements, exemplary values, and messages within such texts. Furthermore, the materials do not fully support the implementation of the *Kurikulum Merdeka* (Independent Curriculum), which emphasizes